Relación entre la satisfacción y la lealtad de los clientes de la empresa comercial Julca, Iquitos 2022 - Julca Payma, Jhon Lander (2023)
This research sought to determine the type of relationship that exists between customer satisfaction and loyalty in the Julca EIRL company in the city of Iquitos. For this purpose, a non-experimental investigation of descriptive - correlational and cross-sectional scope was designed, which had 40 clients of this company as a sample; to whom a questionnaire with responses on a Likert-type scale was applied. The main result establishes that if there is a moderately strong correlation (Rho = 0.624) between customer satisfaction and customer loyalty, with a significance of 0.000; which allows validating the hypothesis of this research, in the sense that there is a positive and significant relationship between both variables. The company is recommended to improve customer satisfaction to increase their loyalty, which would allow it to consolidate its customer portfolio.